Karakteristik Fisikokimia, Kadar Gizi, Organoleptik dan Aktivitas Antioksidan dalam Es Krim Yoghurt Rosela - Farah Diba 'Izzati; Irma Isnafia Arief; Cahyo Budiman; Zaenal Abidin (Jurnal Ilmu Pertanian Indonesia, 2024)
This study develops roselle yogurt ice cream by combining the probiotic benefits of yogurt with bioactive compounds from roselle flowers. Yogurt is produced through milk fermentation by lactic acid bacteria, while roselle flower extract is rich in anthocyanins and flavonoids known for their antioxidant, antibacterial, and anti-inflammatory properties. The research methods included a comprehensive analysis of physicochemical properties, nutritional content, microbiology, antioxidant activity, and organoleptic characteristics. Using a randomized complete design, data analysis employed ANOVA and the Least Significant Difference tests (P < 0.05), with sensory evaluation conducted using the Kruskal-Wallis test. The results of exploring the synergy between roselle yogurt and ice cream in varying proportions (20:80, 30:70, 40:60) showed that the treatment with a 30:70 ratio of roselle yoghurt (P2) was optimal in physicochemical characteristics such as pH 5.47, total titratable acidity 0.74%, overrun 75.61%, and meltdown rate of 26.98 minutes. P2 also exhibited the highest total antioxidant activity at 137 µg/mL, with good sensory acceptance from consumers. This experiment provided an understanding of the potential of roselle yoghurt ice cream as a product that meets increasingly selective consumers' nutritional and health needs. It is hoped that these findings will stimulate the development of ice cream products that are not only commercially popular but also provide significant health benefits. Keywords: roselle yoghurt ice cream, antioxidant activity, consumer health